Resistance to Narratives of the Covid-19 Pandemic as an Act of God - Kamwendo, Zara Thokozani 19XX- (Zygon, 2021)
This article examines the views of 12 bishops of the Church of England in understanding the COVID-19 pandemic from the perspective of divine action. The most consistently mentioned unhelpful narratives hinge on an understanding of the pandemic as an act of God. Although there are several possible contextual explanations for this resistance to understand the pandemic as divine action, an analysis of the data shows that it is grounded in a desire to maintain (1) a space for the pandemic, the suffering, and the virus that caused it to be understood as part of creation and (2) focus on human agency and responsibility as the appropriate response to the pandemic. I argue that the strong resistance among the bishops interviewed to a narrative of divine punishment in particular is ultimately grounded in a desire to disable the blunt but effective tool of making moral judgments in the name of divine authority that regularly follow in the wake of global disasters.